He Representation Of Id, Ego And Superego In Sylvia Plath’S Selected Poems: “A Literary Psychological Approach” - Akso, Al; Efendi, Dedi; Oktariza, Dodi (Krinok:Jurnal Linguistik Budaya, 2025)
This study explains the representation of the id, ego, and superego in selected poems by Sylvia Plath through a literary psychology approach, particularly based on Sigmund Freud's psychoanalytic theory. The purpose of this study is to describe how Plath's inner conflict and psychological turmoil are reflected in her poems, as well as to reveal the messages conveyed through the representation of the id, ego, and superego in the selected poems of Sylvia Plath. The researcher uses a descriptive qualitative method by selecting three poems from The Collected Poems anthology, edited by Ted Hughes: "Dialogue Between a Ghost and a Priest," "Fiesta Melons," and "Mushrooms". The analysis focuses To identifying and describe textual elements that represent the id (instinct and desire), ego (reality and reason), and superego (moral judgment and conscience). The research findings show that the id appears most dominantly in Plath's poems with (11) data, reflecting raw emotions, personal longing, and unresolved trauma. The ego is reflected through rational responses and internal conflicts with (6) data, while the superego appears less frequently with (2) data, primarily related to moral reflection and feelings of guilt. These findings indicate that the selected poems of Sylvia Plath are heavily influenced by her psychological condition, and her poetry serves as a medium for emotional expression shaped by subconscious urges.